Advanced MMC-Based Hydrostatic Bearings for Enhanced Linear Motion in Ultraprecision and Micromachining Applications - Ali Khaghani; Atanas Ivanov; Mina Mortazavi (Micromachines)
This study investigates the impact of material selection on the performance of linear slideways in ultraprecision machines used for freeform surface machining. The primary objective is to address challenges related to load-bearing capacity and limited bandwidth in slow tool servo (STS) techniques. Multi-body dynamic (MBD) simulations are conducted to evaluate the performance of two materials, alloy steel and metal matrix composite (MMC), within the linear slideway system. Key performance parameters, including acceleration, velocity, and displacement, are analyzed to compare the two materials. The findings reveal that MMC outperforms alloy steel in acceleration, velocity, and displacement, demonstrating faster response times and greater linear displacement, which enhances the capabilities of STS-based ultraprecision machining. This study highlights the potential of utilizing lightweight materials, such as MMC, to optimize the performance and efficiency of linear slideways in precision engineering applications.